Pengaruh Penanganan Komplain terhadap Kepuasan Nasabah pada Baitulmaal Muamalat Medan - Syafira, Dinda; Amalia, Alfi (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This study aims to analyze the effect of complaint handling on customer satisfaction at Baitulmaal Muamalat Medan. Customer satisfaction is an important indicator in evaluating the quality of banking services and can affect customer loyalty and retention. Effective handling of customer complaints is a key factor in increasing customer satisfaction. This research uses a survey method by distributing questionnaires to Baitulmaal Muamalat Medan customers. The research sample consisted of 200 randomly selected customers. The collected data were analyzed using multiple linear regression techniques to test the relationship between complaint handling and customer satisfaction. In addition, descriptive statistical analysis was also carried out to analyze the characteristics of respondents. The results showed that complaint handling has a significant positive influence on customer satisfaction at Baitulmaal Muamalat Medan. This finding shows the importance of implementing effective complaint handling practices in Islamic financial institutions. Customers who are satisfied with the complaint handling provided have a tendency to remain loyal customers.